20:30 BRUXSELS TALKS: FICTION AS A METHOD, FICTION AS A FORMAT, FICTION AS A SPACE FOR PARTICIPATION - Anthoni, Ellen; Balwani, Khushboo; Schoffelen, Jessica; Hannes, Karin (Art/Research International)

(untitled) (University of Alberta, 2021)
On the 23rd of January 2020, a radio talk show of the future, 20:30 Bruxsels Talks, took place in Brussels. With guests and artists from the year 2030, it discussed how the transition to a climate-proof city had happened since 2019. In this article, we present and frame the development of the show and provide insight into the participative creation process. The radio show exemplifies (a) how future fiction can be used as a tool to evoke change and (b) how the participatory development of futurist fiction can be used as a method to trigger imagination and conversation on what citizens want for our cities. We argue that there is an opportunity for researchers to explore fiction as a method, as a format and as a space. Foresight practitioners who want to create engaging stories may find inspiration in the body of knowledge of arts-based research and the arts.